Synthesis of Diterpenoid Rosmic Acid Derivatives. (April 2013) - Marrero, Joaquín G.; Andrés, Lucía San; Luis, Javier G.
The partial synthesis of derivatives of the antimicrobial diterpenoid rosmic acid from the abundant diterpenoid car-nosol is described. The key step involved the cleavage of ring C of rosmanol with lead tetraacetate or 7- O -methylrosmanol with mCPBA. Three analogues of rosmic acid, 11, 12-seco-8, 13-abietadien-12, 7:20, 6β-dilacton-11-oic acid methyl ester, 7α- O -methyl-11, 12-seco-11, 12-epoxy-11, 12-dioxo-8, 13-abietadien-20, 6β-olide, its dimethyl ester, and the known methylgaldosol and rosmaquinone were obtained.